2019
DOI: 10.1080/13675567.2019.1604646
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal logistics collaboration: an exploratory study in Morocco’s agri-food supply chains

Abstract: Horizontal logistics collaboration (HLC) practices have gained much attention in recent years as innovative ways for companies to improve their performance. However, literature does not reveal which factors influence the success or failure of HLC, especially in agri-food supply chains (AFSCs) in developing countries. Therefore, this paper aims to investigate HLC in the context of AFSCs in Morocco as a case of a developing country. First, a literature review is performed to develop a conceptual model for HLC co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(80 citation statements)
references
References 52 publications
1
75
0
4
Order By: Relevance
“…Centralised coordination may help in knowledge sharing, capacity enhancement, and information dissemination (Heimeriks and Schreiner 2002). Badraoui, Van der Vorst, and Boulaksil (2020) also highlighted the importance of horizontal collaboration in AFSC. Singh et al (2019) have also observed that the application of IT tools may help in improving coordination in the supply chains.…”
Section: Supply Chain Strategies To Reduce the Impact Of Covid-19 On Afsc (Hows)mentioning
confidence: 99%
“…Centralised coordination may help in knowledge sharing, capacity enhancement, and information dissemination (Heimeriks and Schreiner 2002). Badraoui, Van der Vorst, and Boulaksil (2020) also highlighted the importance of horizontal collaboration in AFSC. Singh et al (2019) have also observed that the application of IT tools may help in improving coordination in the supply chains.…”
Section: Supply Chain Strategies To Reduce the Impact Of Covid-19 On Afsc (Hows)mentioning
confidence: 99%
“…Brown et al [66] explained that the more a firm trusts its partner, the more it becomes emotionally attached to and identifies with its partner, and the more affectively it will commit to its partner. The research by Badraoui et al [67] into Morocco's agri-food supply chains showed that trust enhanced partners' commitment to relationships. Thus, for the E-commerce enterprise, once it has greater trust in its EDSP, it may have a greater willingness to undertake a commitment to that EDSP.…”
Section: Hypothesis 2 (H2)mentioning
confidence: 99%
“…The global sustainability includes economic, social and environmental issues and enforces the firms to re-think and redesign their practices to manage their relationships with suppliers by collaboration or assessment (Ni and Sun 2018). Supplier's collaboration and governance are equally significant to manage their relationship with buyers for providing sustainable outcomes (Reuter et al 2010;Badraoui, Van der Vorst, and Boulaksil 2020;Alghababsheh and Gallear 2020). Due to coronavirus spread, life-threatening environment is persistent all around the world that is coercing undeniable regulations, stringent safety rules, long queue of public, stock out situations, and restricted working hours all together, has brought the whopping responsibility on firm's stakeholders, policymakers and government to manage their SCs in context to social, economic and environmental issues created in the economies (Cohen 2020;Sarkis et al 2020).…”
Section: Introductionmentioning
confidence: 99%